Detection of MDM2/CDK4 Amplification in Lipomatous Soft Tissue Tumors From Formalin-fixed, Paraffin-embedded Tissue: Comparison of Multiplex Ligation-dependent Probe Amplification (MLPA) and Fluorescence In Situ Hybridization (FISH). Issue 2 (February 2015) - Creytens, David; van Gorp, Joost; Ferdinande, Liesbeth; Speel, Ernst-Jan; Libbrecht, Louis
Abstract : In this study, the detection of MDM2 and CDK4 amplification was evaluated in lipomatous soft tissue tumors using multiplex ligation-dependent probe amplification (MLPA), a PCR-based technique, in comparison with fluorescence in situ hybridization (FISH). These 2 techniques were evaluated in a series of 77 formalin-fixed, paraffin-embedded lipomatous tumors (27 benign adipose tumors, 28 atypical lipomatous tumors/well-differentiated liposarcomas, 18 dedifferentiated liposarcomas, and 4 pleomorphic liposarcomas). Using MLPA, with a cut-off ratio of >2, 36/71 samples (22 atypical lipomatous tumors/well-differentiated liposarcomas, and 14 dedifferentiated liposarcomas) showed MDM2 and CDK4 amplification. Using FISH as gold standard, MLPA showed a sensitivity of 90% (36/40) and a specificity of 100% (31/31) in detecting amplification of MDM2 and CDK4 in lipomatous soft tissue tumors. In case of high-level amplification ( MDM2 - CDK4 /CEP12 ratio >5), concordance was 100%. Four cases of atypical lipomatous tumor/well-differentiated liposarcoma (4/26, 15%) with a low MDM2 and CDK4 amplification level ( MDM2 - CDK4 /CEP12 ratio ranging between 2 and 2.5) detected by FISH showed no amplification by MLPA, although gain of MDM2 and CDK4 (ratios ranging between 1.6 and 1.9) was seen with MLPA. No amplification was detected in benign lipomatous tumors and pleomorphic liposarcomas. Furthermore, there was a very high concordance between the ratios obtained by FISH and MLPA. In conclusion, MLPA proves to be an appropriate and straightforward technique for screening MDM2/CDK4 amplification in lipomatous tumors, especially when a correct cut-off value and reference samples are chosen, and could be considered a good alternative to FISH to determine MDM2 and CDK4 amplification in liposarcomas. Moreover, because MLPA, as a multiplex technique, allows simultaneous detection of multiple chromosomal changes of interest, it could be in the future a very reliable and fast molecular analysis on paraffin-embedded material to test for other diagnostically, prognostically, or therapeutically relevant genomic mutations in lipomatous tumors.